JCIM 2021
DOI: 10.46889/jcim.2021.2308
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Infections and Vitamin D Deficiency in Pregnancy

Abstract: Corona virus disease COVID-19 has been a global health threat since November 2019. It has been reported as 6 th cause of global public health emergency by World Health Organisation on January 2020. Serum cholecalciferol or calcidiol is the prime marker for the vitamin D status of a person. It has also been gaining importance in prevention of COVID-19 disease severity. Vitamin D has proven cellular level modulation in both the adaptive and innate immune system through cytokines and regulation of cell signalling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…Since vitamin D has immune-stimulating and antiinflammatory properties, adequate serum levels in vulnerable populations, such as pregnancy, may reduce the transmission of COVID-19 [8]. This is because vitamin D has immune-stimulating and antiinflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since vitamin D has immune-stimulating and antiinflammatory properties, adequate serum levels in vulnerable populations, such as pregnancy, may reduce the transmission of COVID-19 [8]. This is because vitamin D has immune-stimulating and antiinflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…Academics, health planners, and treating clinicians must prioritize research on the level of vitamin D serum and pregnant women with COVID-19 infection because recent epidemiologic studies found a significant correlation between the blood vitamin D serum and the number of COVID-19 fatalities per million [6]. The results of studies on vitamin D deficiency in pregnant women with COVID-19 infection provide evidence-based risk factors [6][7][8][9][10][11][12][13][14]. This study aimed to examine vitamin D deficiency in pregnant women with COVID-19 infection and determine whether it may be involved in the etiology or pathogenesis of the disease.…”
Section: Introductionmentioning
confidence: 99%